Peranan Mahkamah Konstitusi (MK) Dalam Pemilu Serentak Tahun 2019 - Iin Suny Atmadja (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2021)
The 2019 general election is a starting point in holding elections simultaneously which involves the election of all members of the House of Representatives along with regional leaders at all levels, the Regional Representative Council, including the election of the President and Deputy. All parties and circles are required to take responsibility for the success and active role in, without the exception of the formal organizing institutions, which have been strictly regulated by statutory regulations, namely the KPU (General Election Commission) and Bawaslu (General Election Supervisory Body) and the Constitutional Court (MK). The last as the institution that has the authority to resolve disputes over the results of general elections. Through literature research on Indonesian legislation with descriptive analysis, it can be seen that the role of the Constitutional Court in the 2019 simultaneous election contestation has all been regulated in Law which in its implementation is supported by other supporting regulations. there is a clear line of duty and authority from the Constitutional Court compared to the other two institutions that play a role in the election, namely the KPU and Bawaslu.